Utilisation of chitosan extracts from marine life as dentistry biomaterials: Pemanfaatan ekstrak kitosan dari biota laut sebagai biomaterial kedokteran gigi - Saiful, Siti Zaimin Rahmat; Mutmainna, Indah; Indriani, Lenny (Makassar Dental Journal, 2025)
Chitosan as a natural derivative of chitin, shows great potential as a biomaterial in dentistry thanks to its biocompatibility, biode-gradability, and antimicrobial activity. Data shows chitosan is effective at enhancing the healing process, reducing pain, and in-hibiting the growth of pathogenic micro organisms. Recent studies have also shown that chitosan, especially those produced from the shells of marine animals such as shrimps and crabs, have wide applications in orthodontic, endodontic, periodontic, and implantological treatments. The use of chitosan as a natural material in dentistry offers a safe and environmentally friendly alterna-tive to synthetic materials, making it an attractive option for future dental technology development.